Cryoablation of atrial fibrillation with the fourth‐generation balloon: The first reported case. Issue 5 (8th January 2019) - Moltrasio, Massimo; Tundo, Fabrizio; Fassini, Gaetano; Sicuso, Rita; Cellucci, Selene; Tondo, Claudio
Abstract: Cryoballoon ablation was developed as a new treatment for pulmonary vein (PV) isolation and has demonstrated high procedural success and comforting long‐term clinical outcome. However, some improvements are necessary for real‐time visualization of PV signals that appeared important to increase the efficacy and reduce ineffective cryoapplications. We report, for the first time, a cryoablation procedure using the fourth‐generation cryoballoon, describing betterment in vein signal recording and acute procedural success.